2014
DOI: 10.1074/jbc.m114.568907
|View full text |Cite
|
Sign up to set email alerts
|

Using Markov State Models to Develop a Mechanistic Understanding of Protein Kinase A Regulatory Subunit RIα Activation in Response to cAMP Binding

Abstract: Background: Binding four cAMP molecules activates protein kinase A (PKA). Results: Mechanistic Markov models (MM) show that although one cAMP activates one catalytic subunit four are necessary for full activation. Conclusion: Conformational selection is the predominant mechanism in PKA activation, but heterodimer interactions are also required. Significance: This MM provides a mechanistic foundation for systems models of PKA signaling networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…Previous kinetic studies as well as mutations of the essential PBC Arg in CNB-A (Arg209) and CNB-B (Arg333) led to a model for cooperative activation of the RIα holoenzyme where cAMP binds first to CNB-B [27-29]. This mechanism is consistent with the R:C heterodimer structure [1, 2], is supported by urea denaturation studies [30], and was quantitatively confirmed recently by MD simulations [31]. Although the molecular mechanisms are likely different, all ACRDYS1 mutations lead to a desensitized enzyme that is resistant to activation by cAMP, providing further evidence for the “gatekeeper” role of the CNB-B domain.…”
Section: Discussionsupporting
confidence: 53%
“…Previous kinetic studies as well as mutations of the essential PBC Arg in CNB-A (Arg209) and CNB-B (Arg333) led to a model for cooperative activation of the RIα holoenzyme where cAMP binds first to CNB-B [27-29]. This mechanism is consistent with the R:C heterodimer structure [1, 2], is supported by urea denaturation studies [30], and was quantitatively confirmed recently by MD simulations [31]. Although the molecular mechanisms are likely different, all ACRDYS1 mutations lead to a desensitized enzyme that is resistant to activation by cAMP, providing further evidence for the “gatekeeper” role of the CNB-B domain.…”
Section: Discussionsupporting
confidence: 53%
“…Domain-B preference in Holo validates the standing “gate-keeper” theory of PKA RI α , which holds that cAMP binds to CBD-B first. 27 Domain B preference is neutralized in R 2 C 2 Flipback , where both CBD-A and CBD-B bind on the order of ~10 6 M −1 s −1 (Table 1 and Scheme 1). …”
mentioning
confidence: 99%
“…MSMs use discrete-time Markov chain to describe the conformational dynamics of proteins in terms of jumps between the microstates extracted from the simulation data, providing structural, thermodynamic, and long-timescale kinetic information (16,17). For example, this approach was used to examine the activation of PKA regulatory subunit RIα in response to cAMP binding (18). Yang et al (19) carried out a MSM analysis of a simplified coarse-grained model of the catalytic domain of Hck, a member of the Src family of kinases.…”
mentioning
confidence: 99%